Chemokine receptor CCR5 antagonist maraviroc: medicinal chemistry and clinical applications - Xu, Guoyan G; Guo, Jia; Wu, Yuntao (Current topics in medicinal chemistry, 2014)
The human immunodeficiency virus (HIV) causes acquired immumodeficiency syndrome (AIDS), one of the worst global pandemic. The virus infects human CD4 T cells and macrophages, and causes CD4 depletion. HIV enters target cells through the binding of the viral envelope glycoprotein to CD4 and the chemokine coreceptor, CXCR4 or CCR5. In particular, the CCR5-utilizing viruses predominate in the blood during the disease course. CCR5 is expressed on the surface of various immune cells including macrophages, monocytes, microglia, dendric cells, and active memory CD4 T cells. In the human population, the CCR5 genomic mutation, CCR5Δ32, is associated with relative resistance to HIV. These findings paved the way for the discovery and development of CCR5 inhibitors to block HIV transmission and replication. Maraviroc, discovered as a CCR5 antagonist, is the only CCR5 inhibitor that has been approved by both US FDA and the European Medicines Agency (EMA) for treating HIV/AIDS patients. In this review, we summarize the medicinal chemistry and clinical studies of Maraviroc.